Design of Continuously Variable Transmission Sprocket Wheel - Liang Quanbin; Liu Xinqi; Wang Chao; Sun Zhongqian; Li Yingjun (Jixie chuandong)
For variable-speed bicycle need to manually shift， and after the manual shift the resistance ratio does not match the current situation of problem， a set of utilizing the continuity of spring force to realize continuously variable transmission mechanical bicycle scheme of continuously variable transmission device is put forward， and through the spring force direction and the resistance between a change in the direction angle method， make the drive sprocket pitch circle diameter variation with a non-linear relationship between amount of spring compression， increase the effective resistance range of continuously variable transmission. Then the functional relationship between the diameter change of the dividing circle of the active sprocket and the spring compression is obtained through calculation. Finally， the scheme is simulated and the stress cloud diagram is obtained. The simulation results verify the feasibility of the scheme.